Serum Aminotransferases in Chronic Kidney Disease Patients: A Hospital based Comparative Study - Pokhrel, Asmita; Pokhrel, Buddhi Raj; Pandey, Rachana; Malla, Pragya; Sah, Bishesh; Shrestha, Jharana; Khanal, Madhav Prasad (Nepal Medical College Journal, 2023)
Estimation of serum aminotransferase levels play important role in the diagnosis and monitoring of hepatic diseases. Studies suggest that in patients with chronic kidney disease, especially in those under hemodialysis, the reference ranges of the serum aminotransferases might not be reflective of hepatic function. Due to this, diagnosis and management of liver diseases in such patients becomes quite challenging. This study aims to estimate and compare serum aminotransferases levels of hemodialysis patients and healthy controls. Seventy-five patients undergoing hemodialysis in Nepal Medical College Teaching Hospital for at least three months were included in the study as cases and apparently healthy individuals with no active illness and regular medication use for the past three months and were recruited as controls. Predialysis blood samples were drawn and were analyzed for serum aminotransferases and other blood parameters. The median serum AST and ALT values for hemodialysis patients were 15 U/L and 21 U/L, while for the healthy controls, it was 30 U/L and 36 U/L and the differences were statistically significant (p < 0.001). Among the hemodialysis patients, serum AST was positively correlated with eGFR (ρ = 0.247, p = 0.033) and negatively correlated with serum creatinine levels (ρ = -0.307, p = 0.007). Hence, serum aminotransferases levels were found to be low in patients with impaired kidney function compared to those with normal kidney function.